Feeling out of (existential) place: Existential isolation and nonnormative group membership. (June 2022) - Pinel, Elizabeth C.; Helm, Peter J.; Yawger, Geneva C.; Long, Anson E.; Scharnetzki, Liz
Literature devoted to understanding the experiences of individuals who do not fit the cultural mold—those who belong to minority, stigmatized, or underrepresented groups—demonstrates that nonnormative status goes hand in hand with a range of negative outcomes. The current research considers a heretofore unstudied correlate of nonnormative status: existential isolation (the feeling of being alone in one's subjective experience), which differs from feelings of interpersonal isolation (feeling alone with regard to the quantity or quality of one's relationships). Normative, or mainstream, society may not acknowledge the experiences of those holding a nonnormative status, rendering such individuals at risk of developing heightened feelings of existential isolation. Across Studies 1a and 1b, we found consistently higher trait levels of existential isolation (but not interpersonal isolation) among people with a nonnormative group status than among their normative counterparts. This effect appeared whether we looked at nonnormativeness with regard to race, ethnicity, sexual orientation, citizenship, native language, body weight, religious affiliation, or socioeconomic status. Study 2 highlights one correlate of the existential isolation that accompanies nonnormativeness: decreased certainty with respect to judgments of racism. Implications and suggestions for future research are discussed, including addressing the correlational nature of this research and testing potential mechanisms to explain the link between nonnormative status and existential isolation.